2022
DOI: 10.1186/s12870-022-03839-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of yield traits in Egyptian cotton crosses (Gossypium barbdense L.) under normal conditions

Abstract: To generate high-yielding cultivars with favorable fiber quality traits, cotton breeders can use information about combining ability and gene activity within a population to locate elite parents and potential F1 crosses. To this end, in the current study, twelve cotton parents (eight genotypes as female parents and four testers) and their F1 crosses obtained utilizing the linex tester mating design were evaluated for their general and specialized combining abilities (GCA and SCA, respectively) of yield traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…According to fiber trait Table (3), all crosses showed derived positive or negative better parents heterosis effects except for Micronaire reading which was negatively significant better parents heterosis effects for most crosses except for the crosses Giza92 x PimaS4, Giza92 x PimaS6, Giza92 x Australy13 and Giza93 x TNB1 which recorded insignificant better parents heterosis effects. Similar results agreed with those reported by Arif et al , (2022) , Abdel-Aty et al, (2023), Hottigodar et al, (2023) and Parmar et al, (2023) . The GCA and SCA effects of parents and their crosses for different yield contributing traits are presented in Table 4 and Table 5, respectively.…”
Section: Heterosissupporting
confidence: 93%
“…According to fiber trait Table (3), all crosses showed derived positive or negative better parents heterosis effects except for Micronaire reading which was negatively significant better parents heterosis effects for most crosses except for the crosses Giza92 x PimaS4, Giza92 x PimaS6, Giza92 x Australy13 and Giza93 x TNB1 which recorded insignificant better parents heterosis effects. Similar results agreed with those reported by Arif et al , (2022) , Abdel-Aty et al, (2023), Hottigodar et al, (2023) and Parmar et al, (2023) . The GCA and SCA effects of parents and their crosses for different yield contributing traits are presented in Table 4 and Table 5, respectively.…”
Section: Heterosissupporting
confidence: 93%
“…The cotton genotypes G.96, G.92, Karchenky, G.94, G.93, B.B.B, and G.70 had the greatest average values for fiber qualities when compared to the other cotton genotypes. Likewise, a multitude of previous studies have demonstrated comparable patterns in the assessed agro-morphological parameters [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 60%
“…Plant breeders have improved edible oil and seed yield in sunflower by the exploitation of heterosis (Mumtaz et al, 2014). Plant breeding program required information about combining ability, genetic variability and mode of inheritance of desired plant traits for the development of stable and high yielding hybrids through inter-specific hybridization for future cultivation (Abdel-Aty et al, 2023, Mumtaz et al, 2016.…”
Section: Introductionmentioning
confidence: 99%